(untitled) (EU and comparative law issues and challenges series (ECLIC), 2023)
Distance learning tools are not a feature of modern times. However, COVID-19 pandemic boosted its usage and enabled its penetration into higher education. Among various e-learning features, higher education embraced model of Massive Open Online Courses (MOOCs). This paper addresses the very notion of e-learning in law. It focuses on MOOCs from the perspective of educational pedagogy, but more specifically on its usage in legal education. Pros and contras are given based on experience of MOOCs development in the framework of DIGinLaw project.